MODEL UNTUK MENILAI KESIAPAN PEMDA Ã¢â‚¬Å“DKI JAKARTAÃ¢â‚¬Â DALAM PENGEMBANGAN WILAYAH BERBASIS DUNIA USAHA - suharso, puguh (Jurnal Sains dan Teknologi Indonesia, 2009)
Globalisation era is surely passed on and to lead the people of the world into social interactive one another and also economical competitiveness. How far is DKI Jakarta Government preparing to be up against the global competitiveness in the frame-work to manifest improving the standard of living like advanced of society. There are some of indicators to be used as well as criterion to measure an achievement level of effort to be advanced of society, i.e infrastructure which needed by entrepreneur like : permission, taxation, laboract, traffic road, customs and harbor, publics infrastructure servicing, landuse, security condition, business financial access, and business environment condition. It was the research analysis be done by using data gathering from entrepreneur opinion at the operational area. The aim of research analysis is to measure how level of each indicator value has DKI Jakarta Government prepared to be up against the global competitiveness ? The research conclusion says that : DKI Jakarta Government has well enough prepared to be up against the global competitiveness. The weakness indicator is just taxation because its category included in bad (goodless) while the other indicators are well enough. The measuring parameters due to weakness taxationare time necessity for servicing to arrange tax, amount and various of region retribution, amount and various of region tax, and clarity of tax arrangement prucedure.